Differently-charged graphene-based multilayer films by a layer-by-layer approach for oxygen gas barrier application. (15th December 2018) - Liu, Hongyu; Wu, Jianping; Liu, Cuiyun; Pan, Bingli; Kim, Nam Hoon; Lee, Joong Hee
Abstract: Polyelectrolyte-decorated graphene with positive and negative charges was prepared using graphene oxide as a precursor along with polyallylamine hydrochloride and poly (styrenesulfonate sodium) as surface modifiers, respectively. Driven by an electrostatic interaction, the as-obtained polyelectrolyte-decorated graphene sheets were self-assembled via a layer-by-layer method, producing graphene based composite multilayers. Field emission scanning electron microscopy (FE-SEM) images showed that the surface of composite film exhibited a mass of characteristic wrinkles of graphene. Interestingly, the cross-sectional FE-SEM of the film exhibited an unstratified structure, indicating a good dispersion of graphene sheets in the composite film. The results of oxygen gas permeability testing demonstrated that the resulting composite films exhibited excellent oxygen gas barrier properties. The oxygen gas transmission rate (OTR) of the composite film with 24 bilayers was as low as 1.2 cm 3 m -2 d -1 ∙atm −1, exhibiting potential for use in packaging applications.